Jurandir Freire Costa [*]: As faces da violência - Costa, Jurandir Freire (Percurso, 2005)
The first colleague to be interviewed by Percurso was involved, in 1988, with the research for his book on violence. He wanted to understand the milieu in which Psychoanalysis in practiced in Brazil, and the phenomenon of violence was then beginning to gain importance. The interview focuses on Dr. Costa’s theoretical conceptions, on his interest in Ethics – particularly in the ethics of Psychoanalysis – and on other problems he was working on.